ANALISIS PERMITAAN KUNJUNGAN OBJEK WISATA TAMAN MARGA SATWA BUDAYA KINANTAN (TMSBK) KOTA BUKITTINGGI - Rahmad Idil P; Mirna Tanjung; Melti Roza Adry (Universitas Negeri Padang, 2015)
This Study aims to analyze : (1) Effect of travel cost to demand of tourist visits, (2) Effect of individual income to demand of tourist visits, (3) Effect of age to demand of tourist visits, and (4) Effect of previous experience of visiting to demand of tourist visits. (5) Effect of travel cost, income, age, previous experience jointly against to demand of tourist visits in Taman Marga Satwa Budaya Kinantan di Kota Bukitttinggi. The population in this research were visitors of Taman Marga Satwa Budaya Kinantan di Kota Bukitttinggi. With Accidental Sampling Technique so that obtain about 100 respondents. Data collection technique here is to collect data from BPS and from the data collected through the survey respondents questionnaire. Analysis tool used is multiple linear regression analysis with Ordinary Least Square methode ( OLS ) . Results of this study are: Travel costs ( travelcost ) , income ,visiting experience a significant effect on a visit to the Taman Marga Satwa Budaya Kinantan di Kota Bukitttinggi, and age no significant effect on the life of a visit to the Taman Marga Satwa Budaya Kinantan di Kota Bukitttinggi.Keyword : travel cost methode, tourism demand, cosumer surplus